Does the Number of Levels Fused Affect Spinopelvic Parameters and Clinical Outcomes Following Posterolateral Lumbar Fusion for Low-Grade Spondylolisthesis?. Issue 1 (January 2021) - Harada, Garrett K.; Khan, Jannat M.; Vetter, Christian; Basques, Bryce A.; Sayari, Arash J.; Hayani, Zayd; Tchalukov, Konstantin; Louie, Philip K.; Colman, Matthew; An, Howard S.
Study Design: Retrospective cohort. Objectives: To determine how the number of fused intervertebral levels affects radiographic parameters and clinical outcomes in patients undergoing open posterolateral lumbar fusion (PLF) for low-grade degenerative spondylolisthesis. Methods: This was a retrospective cohort study on patients who underwent open PLF for low-grade spondylolisthesis at a single institution from 2011 to 2018. Patients were divided into groups based on number of levels fused during their procedure (1, 2, or 3 or more). Preoperative and postoperative spinopelvic radiographic parameters, patient-reported outcomes (Visual Analog Scale [VAS]-back, VAS-leg, Oswestry Disability Index [ODI]), and postoperative complications were compared. Results: Of the 316 patients eligible (203 one-level, 95 two-level, 18 three or more levels), change in initial postoperative to final pelvic incidence-lumbar lordosis was greatest in 2-level fusions ( P = .039), while 3 or more level fusions had worse final pelvic tilt measures ( P = .021). In addition, multilevel fusions had worse final VAS-back scores (2-level: P = .015; 3 or more levels: P = .011), higher rates of dural tears (2-level: P = .001), reoperation (2-level: P = .039), and discharge to facility (3 or more levels: P = .047) when compared with 1-level fusions. Conclusions: Patients in multilevel fusions experienced less improvement in back pain, had more complications, and were more commonly discharged to a facility compared with single-level PLF patients. These findings are important for operative planning, for setting appropriate preoperative expectations, and for risk stratification in patients undergoing posterior lumbar fusion for low-grade spondylolisthesis.